2017
DOI: 10.19082/4180
|View full text |Cite
|
Sign up to set email alerts
|

The effect of a self-care program based on the teach back method on the postpartum quality of life

Abstract: BackgroundThe postpartum period is a critical stage of life with major changes in the quality of life. Therefore, special consideration is needed to this issue.ObjectiveTo determine the effect of a self-care program based on the Teach Back method on the postpartum quality of life.MethodsThis experimental study was conducted on eighty postpartum women who had given birth in health centers across Darreh Shahr County, Ilam Province, Iran in 2016. The control group received only routine postpartum care according t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
24
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 38 publications
2
24
0
2
Order By: Relevance
“…These conversations seem to grant many women the “permission” they feel they need to prioritize themselves. Moreover, recent literature supports our anecdotal experiences, demonstrating not only that self-care can mitigate and possibly prevent PMADs but also that women are more likely to invest in self-care when it is recommended by a professional (Çapik, Nazik, & Özdemir, 2015; Ghiasvand, Riazi, Hajian, Kazemi, & Firoozi, 2017; Kim & Dee, 2017).…”
Section: Recommendationssupporting
confidence: 82%
“…These conversations seem to grant many women the “permission” they feel they need to prioritize themselves. Moreover, recent literature supports our anecdotal experiences, demonstrating not only that self-care can mitigate and possibly prevent PMADs but also that women are more likely to invest in self-care when it is recommended by a professional (Çapik, Nazik, & Özdemir, 2015; Ghiasvand, Riazi, Hajian, Kazemi, & Firoozi, 2017; Kim & Dee, 2017).…”
Section: Recommendationssupporting
confidence: 82%
“…A study conducted by Nazik and Eryilmaz (2008) in Turkey demonstrated that care given to women in the postpartum period using Orem's self-care model prevented post-partum complications and increased the self-care power of women (7). It can be said that vulnerability in women during this period is associated with reduced selfcare during post-partum (1).…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, the systematic review of Ha Dinh et al [ 35 ] shows that teach-back education improves adherence to treatment regimens, self-management, and self-care and decreases readmission of patients with chronic disease [ 35 ]. Other research studies have shown the effectiveness of teach-back education in self-management in renal transplant recipients [ 36 ], health promotion of diabetic patients [ 37 ], using respiratory inhalers in chronic pulmonary diseases [ 38 ], and postpartum quality of life [ 39 ].…”
Section: Introductionmentioning
confidence: 99%